Analysis of precipitation and recharge of aquifers in Tota and Ibagué (Colombia) from stable isotopes (18O and 2H) - Mariño Martínez, Jorge Eliécer; Veloza Franco, Jairo Alfredo; Martínez Sánchez, Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 61-71).